2019
DOI: 10.1021/acs.chemrestox.9b00042
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry for Investigating the Effects of Toxic Metals on Nucleic Acid Modifications

Abstract: The extensive use of toxic metals in industry and agriculture leads to their wide distribution in the environment, which raises critical concerns over their toxic effects on human health. Many toxic metals are reported to be mildly mutagenic or non-mutagenic, indicating that genetic-based mechanisms may not be primarily responsible for toxic metal-induced carcinogenesis. Increasing evidence has demonstrated that exposure to toxic metals can alter epigenetic modifications, which may lead to the dysregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Nucleic acids typically undergo hydrolysis, resulting in formation of small compounds, such as nucleotides, nucleosides, or nucleobases, followed by the determination of these components with MS ( Figure 5) [164]. The chromatographic retention time, mass-to-charge ratios and fragmentation MS spectra could afford the identification information of components from nucleic acids.…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…Nucleic acids typically undergo hydrolysis, resulting in formation of small compounds, such as nucleotides, nucleosides, or nucleobases, followed by the determination of these components with MS ( Figure 5) [164]. The chromatographic retention time, mass-to-charge ratios and fragmentation MS spectra could afford the identification information of components from nucleic acids.…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…The in vivo abundance of DNA modifications generally is low. , Mass spectrometry (MS) has been widely used in the detection and quantification of DNA modifications as it exhibits high detection sensitivity and powerful capability to identify compounds. , MS-based methods for analyzing DNA modifications have significantly advanced over the past decade, which has greatly stimulated the research on DNA epigenetic modifications. , The emergence of next-generation sequencing technology provides complementary methodology to enable mapping of modifications in genomes, helping to reveal their biological roles . This perspective focuses on the mass spectrometry- and sequencing-based methodologies for the assessment of naturally occurring DNA modifications (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…6,10−13 MS-based methods for analyzing DNA modifications have significantly advanced over the past decade, which has greatly stimulated the research on DNA epigenetic modifications. 14,15 The emergence of next-generation sequencing technology provides complementary methodology to enable mapping of modifications in genomes, helping to reveal their biological roles. 7 This perspective focuses on the mass spectrometry-and sequencing-based methodologies for the assessment of naturally occurring DNA modifications (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition to the genetic-based mechanisms, epigeneticbased mechanisms also play important roles in Cr(VI)-induced cytotoxicity. 15,16 Increasing evidence demonstrates that the status of epigenetic modifications could be affected with exposure to toxic heavy metals, resulting in the abnormal expression of genes. 15,17−19 A recent study indicated that Cr(VI) exposure can alter the DNA methylation status of the DNA repair gene, which therefore can lead to decreased expression of the DNA repair gene and enhanced DNA damages.…”
Section: ■ Introductionmentioning
confidence: 99%